2023
DOI: 10.1039/d3ta00603d
|View full text |Cite
|
Sign up to set email alerts
|

All sprayed fluorine-free membrane electrode assembly for low-platinum and low-humidity proton exchange membrane fuel cells

Abstract: Reducing platinum catalyst loading and humidity dependence of the membrane electrode assemblies (MEAs) is highly desirable for commercializing proton exchange membrane fuel cells (PEMFCs). Meanwhile, replacing the perfluorinated sulfonic-acid PEMs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Recently, Xu et al reported an all-sprayed MEA with a proton exchange membrane fabricated by spraying the catalyst ink and ionomer solution onto the glass plate and then natural shedding after hydration for fuel cells. 15 The use of a glass plate as the substrate to form a 2D glass plate/sprayed CL interface with low adhesion strength is the key to achieving the MEA transfer process. However, 3D-ordered catalytic nanoarrays are not able to grow on the glass plate using an electrodeposition or hydrothermal method.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xu et al reported an all-sprayed MEA with a proton exchange membrane fabricated by spraying the catalyst ink and ionomer solution onto the glass plate and then natural shedding after hydration for fuel cells. 15 The use of a glass plate as the substrate to form a 2D glass plate/sprayed CL interface with low adhesion strength is the key to achieving the MEA transfer process. However, 3D-ordered catalytic nanoarrays are not able to grow on the glass plate using an electrodeposition or hydrothermal method.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Unfortunately, the chemical incompatibility between polymeric ionomers and inorganic catalyst particles will lead to detrimental AEM|CL interface delamination and triple-phase boundary degradation (e.g., ionomers agglomerate and migrate, catalyst particles collapse and disintegrate). 17 Numerous approaches have been adopted to address the MEA interface issues, including physical (interface patterning and interlocking, 18,19 gradient composition design, 20 optimizing MEA fabrication process 21,22 ) and chemical ones (chemical cross-linking, 23,24 self-healing ionomers 25 ). More recently, enhancing the adhesive interaction between ionomers and catalyst particles (metal Pt or Pt-alloys loaded on porous carbon supports) has been identified as a practical approach to reinforce the triple-phase boundary and improve the CL microstructure.…”
Section: ■ Introductionmentioning
confidence: 99%